Peace agreement with GAM: end of the peace process? - Harish, S.P. (2016)
ON MONDAY 15 August 2005, a Memorandum of Understanding (MOU) was signed between the Government of Indonesia (GoI) and the Acehnese separatist group, Gerakan Aceh Merdeka (GAM). This is a historic peace agreement because it is the first accord between GoI and GAM that addresses the substantive issues of the protracted conflict in Aceh.